2022
DOI: 10.1177/07067437221087085
|View full text |Cite
|
Sign up to set email alerts
|

Translation, validation and exploration of the factor structure in the French version of the Posttraumatic Cognitions Inventory (PTCI)

Abstract: Le Posttraumatic Cognitions Inventory (PTCI) is one of the most used instruments to assess posttraumatic cognitions. Since its release, many studies have tried to validate and translate this questionnaire, but they had difficulty to confirm its structure and then suggested alternatives. Faced with no consensus, a short version in nine statements was developed and showed good psychometric properties. To date, no French version of the PTCI has been validated, thereby preventing studies from investigating the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(155 reference statements)
1
5
0
Order By: Relevance
“…The analysis revealed that the 3-factor structure best fitted the data. This is the same as the Wells' PTCI-9 structure model and previous studies that have confirmed 3 factors structure 15,16,23,24 . Although the literature supports the 3 factors model for PTCI-9, the PTCI did not fulfill a consistent factor structure, nor consistent validity in recent studies 23 .…”
Section: Structuresupporting
confidence: 78%
See 2 more Smart Citations
“…The analysis revealed that the 3-factor structure best fitted the data. This is the same as the Wells' PTCI-9 structure model and previous studies that have confirmed 3 factors structure 15,16,23,24 . Although the literature supports the 3 factors model for PTCI-9, the PTCI did not fulfill a consistent factor structure, nor consistent validity in recent studies 23 .…”
Section: Structuresupporting
confidence: 78%
“…The Persian version of PTCI-9 demonstrated strong internal consistency (α=.74); same as the French version of PTCI-9 that has been developed and studied recently (α = .78 to .80). 16 Internal consistency through Cronbach's alpha was confirmed for the total scale and the 3 subscales. This finding supported the original study done by Wells (2019); they found strong internal consistency (α =.87) and also strong associations between PTCI-9 scores and PTSD measures.…”
Section: Reliabilitymentioning
confidence: 79%
See 1 more Smart Citation
“…The Posttraumatic Cognitions Inventory -9 (PTCI-9; Wells et al, 2019 ; Lebel et al, 2022 ) is a nine-item measure of trauma-related negative cognitions that includes three subscales: negative cognitions about the “self” describes a negative view of oneself and a loss of self-trust (e.g., “I feel like I don’t know myself anymore”); negative cognitions about the world focuses on how the world is fundamentally unsafe and others are untrustworthy (e.g., “People can’t be trusted”); lastly, negative cognitions about self-blame suggests that one is to blame for what happened (e.g., “Somebody else would not have gotten into the situation”). Items are rated on a seven-point Likert scale (1 = totally disagree, 7 = totally agree).…”
Section: Methodsmentioning
confidence: 99%
“…The original psychometric study demonstrated a high internal consistency reliability estimate and good convergent and discriminative validity (Foa et al, 1999). To date, the PTCI has been translated into Dutch (van Emmerik et al, 2006), Chinese (Su & Chen, 2008), German (Müller et al, 2010), Hebrew (Daie-Gabai et al, 2011), Turkish (Güleç et al, 2013), Portuguese (Sbardelloto et al, 2013), Korean (Shin et al, 2020), and French (Lebel et al, 2022) and validated in various samples. These findings consistently indicate good psychometric characteristics of the PTCI; however, the factor structure remains controversial.…”
mentioning
confidence: 99%